Legal Aid Implementation in Indonesia: Regulatory Design, Institutional Barriers, and Access to Justice - I Kadek Rico Vergian Dinatha Dinatha; Komang Widiana Purnawan (International Journal of Business, Law, and Education, 2026)
Indonesia constitutionally affirms the rule of law, equality before the law, and equal legal protection. In practice, however, economic inequality, limited legal literacy, uneven institutional distribution, and administrative rigidity continue to restrict access to justice for poor and vulnerable communities. This article analyzes the legal framework governing state-funded legal aid in Indonesia and identifies the principal legal and institutional problems that arise in its implementation. Using a socio-legal design, the study combines statutory analysis of Law No. 16 of 2011 on Legal Aid, Law No. 18 of 2003 on Advocates, Government Regulation No. 42 of 2013, and related instruments with factual analysis of public reports, survey findings, and secondary legal scholarship. The findings show that Indonesia has substantially transformed legal aid from a voluntary pro bono practice into a state responsibility funded through the national budget. Nevertheless, four implementation problems remain salient: the persistence of informal operational charges despite the free-service mandate; ambiguous parameters for identifying eligible poor beneficiaries; low public awareness of free legal aid, with 62.9% of respondents in a 2024 national survey unaware of the service; and a rigid three-year verification and accreditation cycle for legal aid organizations. The article argues that the Indonesian legal aid regime requires more precise eligibility standards, explicit prohibition and monitoring of hidden charges, rolling accreditation, stronger public legal education, and integrated digital outreach. These reforms are necessary to align statutory design with the constitutional promise of equal access to justice.